A combined radial basis function based interpolation method for fluid-structure interaction problems and its application on high-speed trains. (May 2019) - Dou, Weiyuan; Zhang, Lele; Chen, Geng; Zhu, Wenjie
Highlights: A novel combined elemental center and node interpolation (CCNI) was proposed to improve the data transfer accuracy of unidirectional fluid-structure interaction (FSI). Fundamental works were performed by 2D analytic and 3D cases. Using a reasonable weight coefficient in CCNI could reduce the interpolation error in data transfer. CFD simulation of two trains encountering was validated by field experiment. CCNI provides a better solution on data transfer of large mechanical engineering structures than solo node interpolation method. Abstract: In fluid-structure interaction (FSI) problems, accuracy of the data transfer between fluid-structure interfaces is mainly attributed to the element type and discretization density of grids in both fluid and structure domains. To remedy the inaccuracy caused by the prevalently applied solo elemental node interpolation strategy, a novel interpolation method is proposed in the present study. The approach is based on the radial basis function and introduces a weight coefficient through which the centroid and nodes of an element are joined. This way, the interpolation will be conducted in accordance to a weighted summation of both terms. Before it is applied to practice relevant engineering examples, the validity of the formulated approach is first examined by simple 2D and further 3D case studies. Studies have clearly illustrated that, compared to pure element centroid or nodes based interpolation schemes, the established approach is insensitive to the pressure distribution. Meanwhile, in these cases the influence of selected basis functions and mesh densities have been examined in detail. Based on the knowledge gained from these case studies, it further investigated a problem emerged from high-speed trains in which the CFD simulation is validated by the field experiment and the task is to transfer data from the fluid domain to the structure domain. Result of the study shows that for the high speed train model considered which has complicated non-matching grids, the accuracy of data transfer in fluid-structure interaction is highly improved and the maximum of global relative error achieves 2.62%.